1964
DOI: 10.1161/01.cir.29.1.84
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Beta Adrenergic Blockade on the Circulation, with Particular Reference to Observations in Patients with Hypertrophic Subaortic Stenosis

Abstract: The circulatory effects of blocking the beta adrenergic receptors with Nethalide were studied in 10 patients with hypertrophic subaortic stenosis and in five postoperative subjects undergoing right heart catheterization. In the resting state, the heart rate and the rate of pressure development in the right ventricle diminished slightly, but cardiac index was not altered by the administration of Nethalide. These observations suggest that tonic sympathetic activity is not of major importance in basal subjects in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
69
0
5

Year Published

1964
1964
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 219 publications
(74 citation statements)
references
References 23 publications
0
69
0
5
Order By: Relevance
“…Small and mostly retrospective studies suggest that oral propranolol can abolish or reduce resting and provocable LVOTO and provide symptomatic beneit [49,50]. Donald et al's study showed that β-blocker abolished the increase in gradient caused by isoproterenol and, more importantly, halved the increase in gradient caused by exercise [51]. In a 5-year follow-up, a study demonstrated that propranolol signiicantly improved the HCM patient's syndrome (dyspnea, angina, palpitations, dizziness, and syncope) by 58-100% [52].…”
Section: Pharmacology Managementmentioning
confidence: 99%
“…Small and mostly retrospective studies suggest that oral propranolol can abolish or reduce resting and provocable LVOTO and provide symptomatic beneit [49,50]. Donald et al's study showed that β-blocker abolished the increase in gradient caused by isoproterenol and, more importantly, halved the increase in gradient caused by exercise [51]. In a 5-year follow-up, a study demonstrated that propranolol signiicantly improved the HCM patient's syndrome (dyspnea, angina, palpitations, dizziness, and syncope) by 58-100% [52].…”
Section: Pharmacology Managementmentioning
confidence: 99%
“…33,41,65 Reduced inotropy and longer ventricular filling times associated with β-blockade can reduce obstructive symptoms. Some centres have taken the approach of using verapamil as a first-line agent, but this strategy can be associated with acute exacerbation of obstruction due to preferential lowering of systemic vascular resistance.…”
Section: Reviewmentioning
confidence: 99%
“…Pronethalol is effective against ventricular arrhythmias (Harrison, Braunwald, Glick, Mason, Chidsey, and Ross, 1964;Cohen, Effat, Goodwin, Oakley, and Steiner, 1964) and has been used to protect against arrhythmias during operative removal of a phaeochromocytoma (Riddell et al, 1963). Pronethalol antagonizes arrhythmias produced by cardiac glycosides (Stock and Dale, 1963;Vaughan Williams and Sekiya, 1963).…”
Section: Prevention Of Arrhythmiasmentioning
confidence: 99%